Associations Between Hepatic and Pancreatic Steatosis with Lumbar Spinal Bone Marrow Fat: A Single-Center Magnetic Resonance Imaging Study - Abbasoğlu, Akın; Karçaaltıncaba, Musturay; Karaosmanoğlu, Ali Devrim; Özmen, Mustafa Nasuh; Akata, Deniz; İdilman, İlkay S. (Turkish Journal of Gastroenterology, 2023)
Background: To evaluate the associations between hepatic, pancreatic steatosis, and lumbar spinal bone marrow fat determined by magnetic resonance imaging-proton density fat fraction in patients with no known or suspected liver disease. Methods: A total of 200 patients who were referred to our radiology department for upper abdominal magnetic resonance imaging between November 2015 and November 2017 were included in this study. All patients underwent a magnetic resonance imaging-proton density fat fraction on a 1.5-T magnetic resonance imaging system. Results: The mean liver, pancreas, and lumbar magnetic resonance imaging-proton density fat fraction were 7.52 ± 4.82%, 5.25 ± 5.44%, and 46.85 ± 10.38% in the study population. There were significant correlations between liver and pancreas (rs = 0.180, P = .036), liver and lumbar (rs = 0.317, P < .001), and pancreas and lumbar magnetic resonance imaging-proton density fat fraction (rs = 0.215, P = .012) in female patients. A weak correlation was observed between liver and lumbar magnetic resonance imaging-proton density fat fraction (rs = 0.174, P = .014) in the total population. The prevalence of hepatic and pancreatic steatosis was 42.5% and 29%, respectively. The prevalence of pancreatic steatosis (42.9% vs. 22.8%, P = .004) was higher in male patients compared to female patients. In subgroup analysis, in patients with hepatic steatosis, there were higher pancreas magnetic resonance imaging-proton density fat fraction (6.07 ± 6.42% vs. 4.66 ± 4.53%, P = .036) and lumbar magnetic resonance imaging-proton density fat fraction (48.81 ± 10.01% vs. 45.40 ± 10.46%, P =.029) compared to patients without hepatic steatosis. In patients with pancreatic steatosis, there were higher liver (9.07 ± 6.08 vs. 6.87 ± 4.06, P = .009) and lumbar magnetic resonance imaging-proton density fat fraction (49.31 ± 9.13% vs.45.83 ± 10.76%, P = .032) in comparison with patients without pancreatic steatosis. Conclusion: Based on the results of the present study, fat accumulation in liver, pancreas, and lumbar vertebra have associations with more evident in females. Cite this article as: Abbasoğlu A, Karçaaltıncaba M, Karaosmanoğlu AD, Özmen MN, Akata D, İdilman İS. Associations between hepatic and pancreatic steatosis with lumbar spinal bone marrow fat: A single-center magnetic resonance imaging study. Turk J Gastroenterol. 2023;34(6):618-625.